2019
DOI: 10.1080/19396368.2019.1573274
|View full text |Cite
|
Sign up to set email alerts
|

Monosodium glutamate daily oral supplementation: study of its effects on male reproductive system on rat model

Abstract: Monosodium glutamate (MSG) is widely used in food preparation industry and has been consumed regularly. Previous studies had reported on effects of MSG when given at extremely high dosages, the results are not applicable to human equivalent intake. Therefore, the present study aimed to evaluate the effect of MSG on sperm quality and changes in reproductive organs of adult male rats when taken at average human daily intake (ADI). Twenty-four adult male rats were randomly assigned into three groups; NC (Normal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 28 publications
3
33
1
Order By: Relevance
“…Although apoptosis is an essential prerequisite in maintaining the population of Leydig cells and testosterone levels 50 increased apoptosis leads to decline in testosterone production, which may increase germ cell apoptosis and the possibility of infertility 51 . However, other studies showed insignificant changes in testosterone levels following MSG challenge 7 , 52 . This differential response may be due to difference in the experimental design including the dose and duration of exposure.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Although apoptosis is an essential prerequisite in maintaining the population of Leydig cells and testosterone levels 50 increased apoptosis leads to decline in testosterone production, which may increase germ cell apoptosis and the possibility of infertility 51 . However, other studies showed insignificant changes in testosterone levels following MSG challenge 7 , 52 . This differential response may be due to difference in the experimental design including the dose and duration of exposure.…”
Section: Discussionmentioning
confidence: 88%
“…This experimental schedule did not lead to permanent infertility, but the normal morphology of the testis would need a long time to be regained 9 . A dose-dependent differences in the response of reproductive hormone, testicular oxidative status and semen characteristics were noticed in a rat model compromised by MSG indicating that daily oral intake of the higher dose (120 mg/kg BW) for 28 days caused a significant damage to the reproductive performances 7 . Oral supplementation of rats at two age groups with three gradual doses of MSG every 48 h for 6 weeks adversely affected spermatogenesis by disrupting the hypothalamic-pituitary gonadal regulatory axis without direct cyto-toxicological effect on the testis 10 .…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations